The design and evaluation of the outflow structures of an interventional microaxial blood pump - Yun, Zhong; Yao, Jinfu; Wang, Liang; Tang, Xiaoyan; Feng, Yunhao (Frontiers in Physiology, 2023)
Blood pump design efforts are focused on enhancing hydraulic effectiveness and minimizing shear stress. Unlike conventional blood pumps, interventional microaxial blood pumps have a unique outflow structure due to minimally invasive technology. The outflow structure, composed of the diffuser and cage bridges, is crucial in minimizing the pump size to provide adequate hemodynamic support. This study proposed four outflow structures of an interventional microaxial blood pump depending on whether the diffuser with or without blades and cage bridges were straight or curved. The outflow flow structure's effect on the blood pump's hydraulic performance and shear stress distribution was evaluated by computational fluid dynamics and hydraulic experiments. The results showed that all four outflow structures could achieve the pressure and flow requirements specified at the design point but with significant differences in shear stress distribution. Among them, the outflow structure with curved bridges would make the blood dispersed more evenly when flowing out of the pump, which could effectively reduce the shear stress at the cage bridges. The outflow structure with blades would aggravate the secondary flow at the leading edge of the impeller, increasing the risk of flow stagnation. The combination of curved bridges and the bladeless diffuser had a relatively better shear stress distribution, with the proportion of fluid exposed to low scalar shear stress (<50 Pa) and high scalar shear stress (>150 Pa) in the blood pump being 97.92% and 0.26%, respectively. It could be concluded that the outflow structure with curved bridges and bladeless diffuser exhibited relatively better shear stress distribution and a lower hemolysis index of 0.00648%, which could support continued research on optimizing the microaxial blood pumps.